Southwest Research-Extension Center, Field Day 2003 (Kansas Agricultural Experiment Station Research Reports, 2003)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: 2003; SRP910; crops; tillage; irrigation; weed science; insect control